Staphylococcus aureus recovery from environmental and human locations in 2 collegiate athletic teams - Oller, A. R.; Province, L.; Curless, B. (Journal of Athletic Training, 2010)
Context: Staphylococcus aureus is spread via direct contact with persons and indirect contact via environmental surfaces such as weight benches. Athletes participating in direct-contact sports have an increased risk of acquiring S aureus infections.